Advances in Targeted Therapies for Rehumatiod Arthritis: From Biologic to Small Molecule Inhibitors - Mansoor, Wasia; Hassan, Syed Muhammad Zain Ul; Rahman , Aziz ur; Arshad, Anam; Waseem, Syeda Hira; Mujtaba , Muhammad (Indus Journal of Bioscience Research, 2025)
This study aimed to evaluate the knowledge, practices, and perceptions of General Practitioners (GPs) in Punjab, Pakistan, regarding the treatment of rheumatoid arthritis (RA) with biologics and small molecule inhibitors, focusing on patient compliance, disease progression, and treatment outcomes. A total of 108 GPs participated, with data collected through self-administered questionnaires, which were analyzed using descriptive statistics, cross-tabulation, and inferential statistics such as chi-square tests and t-tests. The findings revealed that GPs exhibited good knowledge of biologics, with experienced GPs (11-20 years of practice) showing higher awareness compared to less experienced practitioners. The study also highlighted that oral small molecule inhibitors had higher patient compliance (80%) compared to injectable biologics (60%), likely due to the convenience of oral administration. Both treatments showed significant reductions in disease activity, with injectable biologics demonstrating a more substantial impact on disease progression. The results suggest that while both biologics and small molecule inhibitors are effective in managing RA, patient compliance and treatment convenience are critical factors influencing treatment outcomes. This study provides key insights into the effectiveness, safety, and patient compliance of biologics and small molecule inhibitors in rheumatoid arthritis treatment. Injectable biologics showed a stronger impact on disease progression, while oral inhibitors had higher patient compliance due to convenience. More experienced GPs demonstrated greater knowledge of biologic therapies, emphasizing the need for continuous education. The findings highlight the importance of improving treatment accessibility and ensuring that GPs, especially in underserved areas, receive adequate training for optimal RA management. Future research should focus on long-term outcomes, cost-effectiveness, and patient-centered treatment strategies in RA management.